The Impact of Analytical Review Results, Internal Control Reliability, and Experience on Auditors' Use of Analytical Review - Cohen, Jeffrey; Kida, Thomas (Journal of Accounting Research, 1989)
Jeffrey Cohen, Thomas Kida, The Impact of Analytical Review Results, Internal Control Reliability, and Experience on Auditors' Use of Analytical Review, Journal of Accounting Research, Vol. 27, No. 2 (Autumn, 1989), pp. 263-276